From 3D printing to 4D printing - Abdul Hakim Mustafa (2018)
This report aims to investigate how different 3D printed structures and designs can influence the material’s properties when subjected to external force. It also helps to investigate how this will affect 4D printing through its technical functions of the material after it undergoes certain test. The base material that was used to 3D print the designs and structures is Thermo-Polyurethane (TPU) plastic. The 3D printed pieces are printed to different designs which are a mix of auxetic and normal material. Auxetic material which possesses the traits of a negative Poisson’s ratio and a normal material with a positive Poisson’s ratio. These designs are constructed using SolidWorks software. The designs are then being printed using fused deposition modelling method (FDM). These pieces are then subjected to cyclic tensile test. The base material is also tested on, using the cyclic tensile test. Instron tensile tester and the Shimadzu 10kN unit cell tensile tester are both used to conduct experiment on the design and material.